FACTORS INFLUENCING EFL LEARNERS’ WILLINGNESS TO SPEAK ENGLISH IN THE CLASSROOM - Nailin Nafisah; Ahmad Hilal Madjdi; Fitri Budi; Rismiyanto Rismiyanto (Universitas Islam Nahdlatul Ulama Jepara, 2023)
In the term of English as Foreign Language, the learners have few chances to be exposed to English for communication. A very common problem faced by many EFL teachers in the classroom is the learners have lack willingness to speak. The present study is conducted to know the EFL learners’ perception of factors that influence their willingness to speak English in the classroom. The qualitative research is conducted by having questionnaire with 10 EFL learners in Kudus to discover such factors. Several factors were identified in this research, including topic of discussion, task type, interlocutor, and teacher’s role. It is expected that teachers would choose certain approach aims at facilitating students to participate more during the class.